2021
DOI: 10.17712/nsj.2021.1.20200116
|View full text |Cite
|
Sign up to set email alerts
|

The etiology and risk factors of convulsive status epilepticus in pediatric patients of tertiary center in Saudi Arabia

Abstract: Objectives: To assess the etiology of status epilepticus )SE( among the pediatric patients of a tertiary center in Jeddah, Kingdom of Saudi Arabia )KSA(. Methods: Data from 88 cases was obtained retrospectively from 2006 to 2017 from King Abdulaziz University Hospital )KAUH(. Patients aged between 28 days and 14 years with the symptoms of SE were selected for this study. Original ArticlesResults: The data show that the proportions of SE etiologies were 30.5% for febrile seizure, 11.9% for electrolytes imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
5
9
0
2
Order By: Relevance
“…10 In pediatric patients, SE has been associated with CNS damage, fever, poisoning, systemic infection, low anticonvulsant levels, anatomical brain abnormalities, electrolyte imbalances, and inborn metabolic errors in children. 13,14 In our study, prolonged febrile seizures, meningitis, encephalitis,…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…10 In pediatric patients, SE has been associated with CNS damage, fever, poisoning, systemic infection, low anticonvulsant levels, anatomical brain abnormalities, electrolyte imbalances, and inborn metabolic errors in children. 13,14 In our study, prolonged febrile seizures, meningitis, encephalitis,…”
Section: Discussionmentioning
confidence: 50%
“… 19 Mortality rates are 15% to 20% in adults 12 and 3% to 15% in children. 14 In our study, 18 (19.6%) of 92 patients admitted died during hospitalization, while 74 (80.4%) were discharged from the hospital following successful management. 3% of the subjects became refractory status epileptics.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The results demonstrated that inadequate AED treatment was caused by the use of multiple doses of benzodiazepines, the lack of second-or third-line medicines, or the delayed delivery of second-and third-line pharmaceuticals. While Alyoubi, Reem et al [26] also in Jeddah reported that a febrile seizure was the most frequent cause of convulsive status epilepticus, followed by electrolyte imbalance and hydrocephalus.…”
Section: Resultsmentioning
confidence: 99%
“…(2021) [26] This research was carried out in Jeddah, Saudi Arabia to determine what causes status epilepticus (SE) in pediatric patients. Medical records from the years 2006 to 2017 were used to gather the data.…”
Section: Reemmentioning
confidence: 99%